2018
DOI: 10.3390/nu10111712
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Nutritional Indices on Admission to the Coronary Intensive Care Unit with the Development of Delirium

Abstract: Background: Delirium is a common occurrence in patients admitted to the intensive care unit and is related to mortality and morbidity. Malnutrition is a predisposing factor for the development of delirium. Nevertheless, whether the nutritional status on admission anticipates the development of delirium in patients with acute cardiovascular diseases remains unknown. Objective: This study aims to assess the correlation between the nutritional status on admission using the nutritional index and the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
2
11
1
Order By: Relevance
“…According to the present results, the MNA-SF outperformed GNRI in predicting POD among elderly noncardiac surgical patients. To date, only one study by Sugita, et al compared different screening tools, including the GNRI, PNI and CONUT, for prediction of delirium in coronary intensive care unit patients and they observed no a significant association between GNRI and delirium [36], which is similar to our study. Recently, Chu et al and Mazzola et al used the MNA-SF as a screening tool among orthopedic surgical patients and detected a significant association between MNA-SF and POD [31,37].…”
Section: Discussionsupporting
confidence: 90%
“…According to the present results, the MNA-SF outperformed GNRI in predicting POD among elderly noncardiac surgical patients. To date, only one study by Sugita, et al compared different screening tools, including the GNRI, PNI and CONUT, for prediction of delirium in coronary intensive care unit patients and they observed no a significant association between GNRI and delirium [36], which is similar to our study. Recently, Chu et al and Mazzola et al used the MNA-SF as a screening tool among orthopedic surgical patients and detected a significant association between MNA-SF and POD [31,37].…”
Section: Discussionsupporting
confidence: 90%
“…To date, only one study by Sugita, et al compared different screening tools, including the GNRI, PNI and CONUT, for prediction of delirium in coronary intensive care unit patients. Unlike our study, they failed to find a significant association between GNRI and delirium (34). The difference may be related to the fact that the incidence of delirium (17%) detected in our study is relatively higher than that observed in previous study (9%).…”
Section: Roc Curve Analysiscontrasting
confidence: 99%
“…A study compared the efficiency of GNRI, PNI and CONUT on the prediction of delirium in coronary ICU patients and found no significant difference between PNI and CONUT. 25 However, PNI had the superiority in terms of convenience (CONUT is calculated by the serum albumin, serum total cholesterol and total lymphocyte counts).…”
Section: Discussionmentioning
confidence: 99%